RESPON KONSUMEN STARBUCKS INDONESIA TERHADAP ISU BOIKOT BRAND TERAFILIASI ISRAEL: (Studi Deskriptif Kualitatif Pada Starbucks Coffee) - Ilham Jaelani; Fajar Hariyanto; Ana Fitriana Poerana (Journal Publicuho, 2025)
This study aims to examine the responses of Starbucks Indonesia consumers to the boycott issue involving brands affiliated with Israel. The boycott emerged as a form of solidarity with the humanitarian conflict in Palestine and sparked public debate regarding ethical consumption and loyalty to global brands. This research uses a descriptive qualitative approach, involving eight informants who are active Starbucks consumers in Indonesia. Data were collected through in-depth interviews, observation, and document studies, and analysed using thematic methods. The findings show that consumer responses fall into three main categories: (1) consumers who remain loyal due to considerations of product quality and lifestyle; (2) consumers who take a neutral stance by occasionally purchasing while also supporting local products; and (3) consumers who refuse to buy as a form of social and religious concern. These findings indicate that consumer decisions regarding boycott issues are influenced by individual perceptions, social values, and emotional attachment to the brand. This study is expected to contribute to consumer behaviour research, particularly in the context of socio-political issues that affect preferences toward global brands.